The seasonal behavior of the liquidity premium in asset pricing - Eleswarapu, Venkat R.; Reinganum, Marc R. (Journal of Financial Economics, 1993)
This paper empirically investigates the seasonal behavior of the liquidity premium in asset pricing. The evidence suggests a strong seasonal component. In the 1961–1990 period, the liquidity premium is reliably positive only during the month of January. For the non-January months, one cannot detect a positive liquidity premium. The impact of the relative bid-ask spreads on asset pricing in non-January months cannot be reliably distinguished from zero. In contrast to Amihud and Mendelson (1986), however, our evidence suggests that the size effect is significant, even after controlling for spreads.